2010
DOI: 10.3892/or_00001026
|View full text |Cite
|
Sign up to set email alerts
|

Sodium valproate, a histone deacetylase inhibitor, augments the expression of cell-surface NKG2D ligands, MICA/B, without increasing their soluble forms to enhance susceptibility of human osteosarcoma cells to NK cell-mediated cytotoxicity

Abstract: Abstract. MHC class I-related chain molecules A and B (MICA and B) expressed on the cell-surface of tumor cells are ligands for an activating receptor, NKG2D, expressed on natural killer (NK) cells and stimulate the NK cell-mediated cytotoxicity. On the other hand, the soluble form of MICA and B produced by proteolytic cleavage of cell-surface MIC interferes with NK cell-mediated cytotoxicity. We investigated effect of sodium valproate (VPA), a histone deacetylase inhibitor, on the production of cell-surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 18 publications
7
30
0
Order By: Relevance
“…Culture with 1.0 mM VPA increased the expression of MICA/B on the surface of osteosarcoma cells and inhibited their secretion of soluble MICA and MICB, confirming the results of our previous report (16). Our previous study showed that 1.0 mM VPA increased the acetylation of histones, suggesting that at least a part of the action of VPA can be ascribed to its action as a HDAC inhibitor (16).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Culture with 1.0 mM VPA increased the expression of MICA/B on the surface of osteosarcoma cells and inhibited their secretion of soluble MICA and MICB, confirming the results of our previous report (16). Our previous study showed that 1.0 mM VPA increased the acetylation of histones, suggesting that at least a part of the action of VPA can be ascribed to its action as a HDAC inhibitor (16).…”
Section: Discussionsupporting
confidence: 80%
“…After 24 h (day 0), VPA was added to the medium at 1.0 mM, and the cells were cultured for another 7 days, with a medium change on day 3. The cells were detached from the dishes, and the expression of membrane-bound MICA/B was analyzed by a flow cytometric analysis, as described previously (16). The percentages of membrane-bound MICA/B-positive cells were determined by flow cytometric analysis, and the effects of VPA were evaluated by determining the ratio of the percentage of positive cells in the treated cultures to the average percentage of positive cells in the untreated control cultures.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated that HDAC inhibitors stimulate the expression of cell-surface MICA and MICB in a variety of tumors, enhancing the susceptibility of tumor cells to NK cell-mediated cytotoxicity (17)(18)(19)(20)(21). These agents also enhance the expression of cell-surface Fas (22,23), and increase the (24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%